Views across the boundary: School-based co-teachers experiences with co-teaching in initial teacher education - Cooper, Rebecca; Marangio, Karen (Frontiers in Education, 2022)
School and University partnerships are widely promoted as an effective means to support the preparation of pre-service teachers. However, these partnerships are rarely conceived with practicing teachers working in a university context as co-teachers with university teacher educators. School-based co-teachers (practicing teachers who contribute to initial teacher education by teaching alongside university-based teacher educators) contribute to initial teacher education through their support for curriculum and assessment development, providing opportunities for observation and experiences in schools, and teaching with university teacher educators. However, the role of a school-based co-teacher requires some careful navigation and negotiation of the educational spaces that a school-based co-teacher must cross as they teach in university classrooms and foster a co-teaching relationship. This research articulates the process of boundary crossing that four school-based co-teachers undertook as they supported the development of pre-service science teachers. Boundaries exist between the practices and perspectives of teaching school science students and teaching science pre-service teachers at university. Data were collected from four school-based co-teachers across one academic year, including an initial survey at the beginning of the year, an interview at the end of the year, and documentation from co-teaching meetings across the year. An inductive thematic approach was taken to analyze the data. Five themes were identified that describe the ways school-based co-teachers viewed their role as a co-teacher and their associated learning in this role. Drawing on literature around boundary-crossing dialogical learning mechanisms, the themes are described with illustrative excerpts to represent the range of school-based co-teachers experiences. Our data indicates that school-based co-teachers found many opportunities to share their wealth of knowledge and experience with pre-service science teachers but also identified, and often sought out, opportunities to professionally learn and grow. Findings include the importance of sharing aims and purposes to understand the context and the generation of shared knowledge through peer reflection on teaching. This paper offers insights to others who are looking to form and sustain productive relationships with school-based co-teachers to support learning for pre-service teachers in initial teacher education courses.